LEGAL REVIEW OF THE MECHANISM OF ISSUANCE OF REPLACEMENT CERTIFICATES FOR DAMAGED LAND RIGHTS BASED ON GOVERNMENT REGULATION NUMBER 24 OF 1997 CONCERNING LAND REGISTRATION - Al-Anshori, Huzaimah; Chasanah, Nur; Setyawan, David Novan; Manfaluthi, Agus (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
A replacement certificate is a copy of a damaged or lost certificate in terms of meaning and the contents contained therein are not much different from a land title certificate. The results of this study are (1) The mechanism for issuing replacement certificates due to loss, damage and old forms. This replacement certificate is intended for people who have lost their certificates, damaged, torn or missing parts and for those who have certificates with old and obsolete forms so that they need to register a replacement Land Title Certificate, that the mechanism for issuing replacement certificates has been regulated in Chapter IV Article 57-60 of Government Regulation Number 24 of 1997. (2) Implementation of Issuance of Replacement Land Title Certificates Due to Damage. An application can be submitted to the Land Office in its jurisdiction and with the requirements that have been determined by laws and regulations. (3) Legal Protection for Holders of Replacement Land Title Certificates. Legal protection for holders of replacement land title certificates is basically the same as legal protection for land titles in general, where the certificates are both proof of rights, which serve as strong evidence. This is regulated in Law Number 5 of 1960 concerning Basic Agrarian Principles, Article 19.